Microparticles of at least one of expanded ground perlite, diatomaceous earth and sepiolite as absorbent
By granulating the expanded grinding perlite, diatomaceous earth and sepiolite particles with the binder to form particulate products, the problems of unstable fluidity and high dust levels when the liquid absorption amount increases are solved, and the effects of high absorption capacity and stable fluidity are achieved.
Patent Information
- Application Number
- CN202380056651.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Priority Date
- 2022-07-29
- Filing Date
- 2023-06-15
- Publication Date
- 2025-03-18
AI Technical Summary
The existing expansion grinding perlite products have unstable fluidity when the liquid absorption increases and the dust level is high, making it difficult to meet the needs of improving absorption capacity and fluidity.
By granulating the expansion-ground perlite particles, diatomaceous earth particles and sepiolite particles with a binder, a particulate product with high absorption rate, constant fluidity and low dust levels are formed.
It has achieved high absorption capacity, stability of fluidity and reduced dust levels of particulate products, and is suitable for a variety of application scenarios, such as animal feed and fluid spillover treatment.
Smart Images

Figure BDA0005257989580000121 
Figure BDA0005257989580000161 
Figure HDA0005257989590000011
Abstract
Description
Technical Field
[0001] The present disclosure relates to granulates comprising a binder and at least one of expanded ground perlite particles, diatomaceous earth particles and sepiolite particles, methods of making the granulate material, absorbent materials comprising the granulate material, animal feed compositions comprising the granulate material and methods of treating fluid spills using the granulate material. Background Art
[0002] Perlite is a naturally occurring amorphous volcanic glass that has a relatively high water content. When heated rapidly, the water turns to steam and expands the glass to form a foam structure. The lightweight expanded perlite foam structure is ground and classified to suit a wide variety of applications.
[0003] Expanded ground perlite is often used as a lightweight absorbent material in applications where absorption of a targeted liquid is required. Expanded ground perlite has been used as a carrier in animal feed to absorb liquid nutrients. Additionally, expanded perlite is an ideal medium for cleaning fluid spills.
[0004] Diatomaceous earth products are obtained from diatomaceous earth (also called "DE" or "diatomite"), which is generally known as sediments rich in biogenic silica (silicon dioxide produced or brought by living organisms) in the form of the siliceous skeletons (siliceous shells) of diatoms. Diatoms are a diverse array of microscopic, unicellular, golden-brown algae, generally belonging to the class Bacillariophyta, which have an ornate siliceous skeleton of a diverse and complex structure containing two valves, which in living diatoms fit together much like a pill box. Diatomaceous earth can be formed from the remains of aquatic diatoms, and therefore, diatomaceous earth deposits can be found near current or former bodies of water. These deposits are generally divided into two categories based on their source: freshwater and saltwater
[0005] Sepiolite is a fibrous hydrated magnesium silicate that is opaque and white, gray, or cream in color. This light, porous clay is said to resemble sea foam. Sepiolite, like ground perlite, is known to have good adsorption properties and is a material available in large quantities.
[0006] It is desirable to produce a microgranular product comprising at least one of expanded ground perlite particles, diatomaceous earth particles and sepiolite particles and a binder, which microgranular product has improved absorption capacity, maintains constant fluidity when the liquid incorporation amount increases, and has reduced dust levels compared to the commonly used expanded perlite. Summary of the invention
[0007] According to a first aspect, there is provided a microparticle comprising at least one of expanded ground perlite particles, diatomaceous earth particles and sepiolite particles and a binder, wherein:
[0008] i) D of the expanded and ground perlite particles 50 From about 5 microns to about 40 microns;
[0009] ii) D of the diatomaceous earth particles 50 From about 5 microns to about 40 microns;
[0010] iii) D of the sepiolite particles 50 From about 5 microns to about 100 microns;
[0011] iv) D of the microparticles 50 From about 150 microns to about 2000 microns; and
[0012] The particles are bonded together by the binder, forming pores between the particles.
[0013] According to a second aspect, there is provided an absorbent material comprising particles according to the first aspect.
[0014] According to a third aspect, there is provided a method for handling a fluid spill, the method comprising applying an absorbent material according to the second aspect to the fluid spill such that the fluid is absorbed by the absorbent material.
[0015] According to a fourth aspect, there is provided an animal feed composition comprising microparticles according to the first aspect.
[0016] According to a fifth aspect, there is provided a method of preparing microparticles according to the first aspect, comprising spray drying ground expanded perlite particles together with a binder and subjecting the mixture to a curing step.
[0017] Those skilled in the art will appreciate that, unless mutually exclusive, the features described in any one of the above aspects may be applied to any other aspects after making necessary modifications in detail. In addition, unless mutually exclusive, any feature described herein may be applied to any aspect and / or combined with any other feature described herein. BRIEF DESCRIPTION OF THE DRAWINGS
[0018] Embodiments will now be described, by way of example only, with reference to the accompanying drawings, in which:
[0019] Figure 1 is a graph showing the effect of absorption on the flowability of powder samples prepared according to the present invention compared to comparative examples.
[0020] Figure 2 Included are SEM images showing various ground expanded perlite particles formed according to the present invention. DETAILED DESCRIPTION
[0021] It has surprisingly been found that granulating at least one of expanded ground perlite, diatomaceous earth and sepiolite using a binder produces a product having a high absorption rate, constant flowability and minimal dust levels.
[0022] Expanded ground perlite particles
[0023] Perlite generally contains the following components: silicon dioxide, aluminum oxide, sodium oxide, potassium oxide, iron oxide, magnesium oxide, calcium oxide, water and small amounts of other metal elements.
[0024] The perlite particles of the present invention are in the form of expanded perlite. Typically, the expanded perlite includes one or more cells or a portion of a cell, wherein a cell is a void space partially or completely surrounded by a glass wall, typically formed by the expansion of a gas when the glass is in a softened state. A method of expanding the perlite may include heating the perlite in air in an expansion furnace to a temperature of at least about 700° C., typically between 800° C. and 1100° C. Exemplary methods for producing expanded perlite are described in US2006 / 0075930, the entire contents of which are incorporated herein by reference. The bulk volume of the expanded perlite is typically up to 20 times that of the unexpanded material.
[0025] According to the invention, the perlite is ground after expansion in an expansion furnace.
[0026] Unless otherwise stated, the particle size properties of expanded ground perlite particles referred to herein are measured by methods employed in the art of laser scattering, using a CILAS 1064L particle size analyzer provided by CILAS (or by other methods that give essentially the same results). In the laser scattering technique, based on the application of Fraunhofer and Mie theory, the diffraction of a laser beam can be used to measure the size of particles in powders, suspensions, and emulsions. This machine provides for the measurement and mapping of the cumulative volume percentage of particles having a size less than a given esd value, referred to in the art as the "equivalent spherical diameter" (esd). The average particle size D 50 is the esd value of a particle determined in this way, where 50% by volume of the particles have a D less than 50 The equivalent spherical diameter of the value.
[0027] According to the present invention, the D of the expanded ground perlite particles 50 From about 5 to about 40 microns, such as from about 10 to about 35 microns, or from about 15 to about 30 microns, or from about 20 to about 25 microns.
[0028] In certain embodiments, the bulk density of the expanded ground perlite particles is about 0.05 g / cm 3 To about 0.20g / cm 3 , for example about 0.06 g / cm 3To about 0.19g / cm 3 , for example, about 0.07 g / cm 3 To about 0.18g / cm 3 , for example, about 0.08 g / cm 3 To about 0.17g / cm 3 , for example, about 0.09 g / cm 3 To about 0.16g / cm 3 , for example, about 0.10 g / cm 3 To about 0.15g / cm 3 , for example, about 0.11 g / cm 3 To about 0.14g / cm 3 , for example, about 0.12 g / cm 3 To about 0.13g / cm 3 .
[0029] Diatomaceous earth particles
[0030] Unless otherwise stated, the particle size properties of diatomaceous earth particles referred to herein are measured by methods employed in the art of laser scattering, using a CILAS 1064L particle size analyzer provided by CILAS (or by other methods that give essentially the same results). In the laser scattering technique, based on the application of Fraunhofer and Mie theory, the diffraction of a laser beam can be used to measure the size of particles in powders, suspensions, and emulsions. This machine provides for the measurement and mapping of the cumulative volume percentage of particles having a size less than a given esd value, referred to in the art as the "equivalent spherical diameter" (esd). The average particle size D 50 is the esd value of a particle determined in this way, where 50% by volume of the particles have a D less than 50 The equivalent spherical diameter of the value.
[0031] According to the present invention, the D 50 From about 5 to about 40 microns, such as from about 10 to about 35 microns, or from about 15 to about 30 microns, or from about 20 to about 25 microns.
[0032] In certain embodiments, the diatomaceous earth particles have a bulk density of about 0.05 g / cm 3 To about 0.20g / cm 3 , for example about 0.06 g / cm 3 To about 0.19g / cm 3 , for example, about 0.07 g / cm 3 To about 0.18g / cm 3 , for example, about 0.08 g / cm 3 To about 0.17g / cm 3, for example, about 0.09 g / cm 3 To about 0.16g / cm 3 , for example, about 0.10 g / cm 3 To about 0.15g / cm 3 , for example, about 0.11 g / cm 3 To about 0.14g / cm 3 , for example, about 0.12 g / cm 3 To about 0.13g / cm 3 .
[0033] Sepiolite granules
[0034] Sepiolite is a naturally occurring clay mineral. It is a hydrated magnesium silicate that is lightweight, non-swelling and porous.
[0035] The particle size properties of the sepiolite particles mentioned herein are measured by methods employed in the field of laser scattering, using a CILAS 1064L particle size analyzer provided by CILAS (or by other methods that give substantially the same results). In the laser scattering technique, based on the application of Fraunhofer and Mie theory, the diffraction of a laser beam can be used to measure the particle size in powders, suspensions and emulsions. This machine provides measurement and mapping of the cumulative volume percentage of particles having a size less than a given esd value (referred to in the art as "equivalent spherical diameter" (esd)). The average particle size D 50 is the esd value of a particle determined in this way, where 50% by volume of the particles have a D less than 50 The equivalent spherical diameter of the value.
[0036] According to the present invention, the D 50 From about 5 to about 100 microns, for example, from about 10 to about 90 microns, or from about 20 to about 80 microns, or from about 30 to about 70 microns, or from about 40 to about 60 microns, from about 10 to about 50 microns, or from about 20 to 40 microns.
[0037] In certain embodiments, the bulk density of the sepiolite particles is about 0.05 g / cm 3 To about 0.30g / cm 3 , for example about 0.06 g / cm 3 To about 0.19g / cm 3 , for example, about 0.07 g / cm 3 To about 0.18g / cm 3 , for example, about 0.08 g / cm 3 To about 0.17g / cm 3 , for example, about 0.09 g / cm 3 To about 0.16g / cm3 , for example, about 0.10 g / cm 3 To about 0.15g / cm 3 , for example, about 0.11 g / cm 3 To about 0.14g / cm 3 , for example, about 0.12 g / cm 3 To about 0.13g / cm 3 .
[0038] Granulation
[0039] According to the present invention, at least one of expanded ground perlite particles, diatomaceous earth particles and sepiolite particles are bound together using a binder to form granules. Granulation is the act or process in which primary powder particles adhere to form larger multi-particle entities called granules.
[0040] In certain embodiments, the microparticles comprise, consist of, or consist essentially of expanded ground perlite particles and a binder. In certain embodiments, the microparticles comprise, consist of, or consist essentially of diatomaceous earth particles and a binder. In certain embodiments, the particles comprise, consist of, or consist essentially of sepiolite particles and a binder. In certain embodiments, the particles comprise, consist of, or consist essentially of sepiolite particles and a binder. In certain embodiments, the particles comprise, consist of, or consist essentially of a blend of expanded ground perlite particles and diatomaceous earth particles and a binder. In certain embodiments, the particles comprise, consist of, or consist essentially of a blend of expanded ground perlite particles and sepiolite particles and a binder. In certain embodiments, the particles comprise, consist of, or consist essentially of a blend of expanded ground perlite particles and sepiolite particles and a binder. In certain embodiments, the particles comprise, consist of, or consist essentially of a blend of diatomaceous earth particles and sepiolite particles and a binder. In certain embodiments, the particles comprise, consist of, or consist essentially of a blend of expanded ground perlite particles and sepiolite particles and a binder. In certain embodiments, the particles comprise, consist of, or consist essentially of a blend of expanded ground perlite particles, diatomaceous earth particles, and sepiolite particles and a binder.
[0041] At least one of the expanded ground perlite particles, diatomaceous earth particles, and sepiolite particles are bound together by a binder to form pores or otherwise referred to as interstitial void spaces between the particles. In some embodiments, the pores have a measurable pore size, which is explained in the experimental section below. In certain embodiments, the median pore size is about 1 g / cm 3 To about 6g / cm 3 , or about 1.1 g / cm 3 , or about 1.2g / cm 3 , or about 1.3g / cm 3 , or about 1.4g / cm 3 , or about 1.5g / cm 3, or about 1.6g / cm 3 , or about 1.7g / cm 3 , or about 1.8g / cm 3 , or about 1.9g / m 3 , or about 2.0g / m 3 .
[0042] According to the present invention, the D 50 The present invention relates to a nanostructured carbon foam having a thickness of about 150 to about 2000 microns, for example, about 200 microns to about 1900 microns, or about 300 microns to about 1800 microns, or about 400 microns to about 1700 microns, or about 500 microns to about 1600 microns, or about 600 microns to about 1500 microns, or about 700 microns to about 1400 microns, or about 800 microns to about 1300 microns, or about 900 microns to about 1200 microns, or about 1000 microns to about 1500 microns. About 1100 microns, or about 200 microns to about 600 microns, such as about 350 microns to about 550 microns, or about 400 microns to about 500 microns, or about 600 microns to about 1900 microns, such as about 700 microns to about 1800 microns, or about 800 microns to about 1600 microns, or about 900 microns to about 1500 microns, or about 1000 microns to about 1400 microns, or about 1100 microns to about 1300 microns. By laser, the particle D 50 It may be from about 200 microns to about 1000 microns, or from about 300 microns to about 900 microns, or from about 400 microns to about 800 microns, or from about 500 microns to about 700 microns.
[0043] In certain embodiments, the bulk density of the particles is about 0.1 g / cm 3 To about 0.50g / cm 3 , for example about 0.15 g / cm 3 To about 0.45g / cm 3 , for example, about 0.20 g / cm 3 To about 0.40g / cm 3 , for example, about 0.20 g / cm 3 To about 0.35g / cm 3 , for example, about 0.25 g / cm 3 To about 0.30g / cm 3 .
[0044] The particles of the present invention may have a measurable BET surface area. The BET specific surface area refers to the surface area of the particles relative to a unit mass of the granular particles, which is determined according to the BET method by the amount of nitrogen adsorbed on the surface of the particles to form a monomolecular layer that completely covers the surface (measured according to the BET method, AFNOR standards X11-621 and 622 or ISO 9277). The details of the BET specific surface area measurement method used in the preparation of the present application are described in the examples.
[0045] The BET specific surface area of the particles may be not less than about 1.5 m 2 / g, for example, not less than about 1.6 m 2 / g, or not less than about 1.7m 2 / g, or not less than about 1.8m 2 / g, or not less than about 1.9m 2 / g, or not less than about 2.0m 2 / g, or not less than about 2.5m 2 / g, or not less than about 3.0m 2 / g, or not less than about 5.0m 2 / g, or not less than about 10m 2 / g (e.g. 10.0m 2 / g), or not less than about 20m 2 / g (e.g. 11.0m 2 / g). The particles may have a size of no greater than about 50 μm 2 / g (e.g. 50.0m 2 / g) of BET specific surface area. For example, not more than about 40m 2 / g (e.g. 40.0m 2 / g), or not more than about 30m 2 / g (e.g. 30.0m 2 / g), or not more than about 20m 2 / g (e.g. 20.0m 2 / g), or not more than about 15m 2 / g (e.g. 15.0m 2 / g), or not more than about 12m 2 / g (e.g. 12.0m 2 / g), or not more than about 11m 2 / g (e.g. 11.0m 2 / g), or not more than about 10m 2 / g (e.g. 10.0m 2 / g), or not more than about 8.0m 2 / g, or not more than about 7.0m 2 / g, or not more than about 6.0m 2 / g. The BET specific surface area of the microparticles can be about 1.5 m 2 / g to about 50m 2 / g (e.g. 50.0m 2 / g), for example, about 2m 2 / g to about 40m 2 / g (e.g. 40.0m 2 / g), or about 5m 2 / g to about 30m 2 / g (e.g. 30.0m 2 / g), or about 10m 2 / g to about 20m 2 / g (e.g. 20.0m 2 / g).
[0046] In certain embodiments, the microparticles have an angle of repose of up to about 38°, as measured by angle of repose (funnel method) using an EFT-01 powder flow tester; the particles have an absorption capacity of at least 150%, as measured using the Westinghouse method described in the experimental part of this article and using dioctyl adipate as the absorbate; and a dust content of less than 10, as measured by a dust analyzer DustmonRD100.
[0047] The angle of repose of a particulate material is the steepest angle of descent or dip, relative to a horizontal plane, to which the material can be piled without collapsing. The morphology of the material affects the angle of repose. When bulk granular material is dumped onto a horizontal surface, a conical pile will form. The internal angle between the surface of the pile and the horizontal plane is called the angle of repose and is related to the density, surface area and shape of the particles and the coefficient of friction of the material. Materials with a low angle of repose form a flatter pile than materials with a high angle of repose. Thus, smooth, rounded grains of sand cannot be piled as steeply as rough, interlocking sand. The method used to calculate the angle of repose is described in more detail in the experimental section below.
[0048] In some embodiments, the angle of repose (of the dry product) is at most about 38°, such as at most 37°, such as at most 36°, such as at most 35°, such as at most 34°, such as at most 33°, such as at most 32°, such as at most 31°, such as at most 30°.
[0049] In certain embodiments, the particles have an advantageously low dust content of less than 10, such as less than 9 or 8 (measured using a dust analyzer Dustmon RD 100 (available from ) measurement). The method used to calculate the dust content values is explained in more detail in the experimental part.
[0050] Expanded ground perlite, diatomaceous earth and sepiolite are known for their ability to retain water and strong water absorption capacity. The absorption capacity is further increased by granulating at least one of the expanded ground perlite particles, diatomaceous earth particles and sepiolite particles with a binder.
[0051] In certain embodiments, the microparticles of the present invention have an absorptive capacity of at least 150% (calculated as 100 x (weight of absorbate / weight of composition)) as measured using the Westinghouse method described in the experimental section herein. In certain embodiments, the absorptive capacity of the microparticles is at least 200%, such as at least 250%, such as at least 300%, such as at least 350%, such as at least 400%, such as at least 450%, such as at least 500%.
[0052] Adhesives
[0053] According to the present invention, at least one of expanded ground perlite particles, diatomaceous earth particles, and sepiolite particles are bound together using a binder to form microparticles.
[0054] In certain embodiments, the binder is a polymer, bentonite, or lignin sulfonate.
[0055] In certain embodiments, the binder is a polymer.
[0056] In certain embodiments, the binder consists of a single type of polymer, or in certain embodiments, the binder comprises one or more polymers.
[0057] In certain embodiments, the polymer is selected from one or more of a water-soluble synthetic polymer, a natural water-soluble polymer, and a polyol. In certain embodiments, the polymer is a combination of these types of polymers.
[0058] In certain embodiments, the binder comprises or consists of a water-soluble synthetic polymer selected from, for example, polyvinyl alcohol (PVA), polyethylene glycol, urea-formaldehyde, polyacrylamide, microcrystalline cellulose, polyacrylate, acrylic acid / maleic acid copolymer, and polyvinyl pyrrolidone.
[0059] In certain embodiments, the binder comprises or consists of a natural water-soluble polymer, for example, xanthan gum, sodium alginate, potassium alginate, lignin sulfonate, locust bean gum, pectin, dextran, carrageenan, agar, xanthan gum, guar gum, gum arabic (acacia), cellulose ethers such as methylcellulose and ethylcellulose, starch or starch-based derivatives.
[0060] In certain embodiments, adhesive comprises polyol or is made up of polyol.Term " polyol " refers to the organic compound containing multiple hydroxyl groups.Polyol can be low molecular weight polyol, for example glycerine or pentaerythritol.Or, polyol can be sugar alcohol, it is a kind of low molecular weight polyol obtained by hydrogenation of sugar, for example erythritol, hydrogenated starch hydrolysate, isomalt, lactitol, maltitol, mannitol, sorbitol and xylitol.The derivative of polyol is also intended to be included in this definition, for example, sorbitan monolaurate, it is the mixture of ester formed by fatty acid lauric acid and the polyol derived from sorbitol.
[0061] In certain embodiments, the binder is selected from polyvinyl alcohol, sodium alginate, potassium alginate, lignin sulfonate, urea-formaldehyde, agar, carrageenan, guar gum, cassia gum, xanthan gum, cellulose, gum arabic (gum arabic), microcrystalline cellulose, methyl cellulose, ethyl cellulose, sorbitan monolaurate, starch or starch-based derivatives, bentonite, and combinations thereof.
[0062] In certain embodiments, the binder comprises or consists of polyvinyl alcohol, preferably having a molecular weight greater than about 90,000 g / mol, or greater than about 100,000 g / mol, or greater than about 120,000 g / mol, or greater than about 150,000 g / mol.
[0063] In some embodiments, the adhesive is a cross-linked adhesive, which is the reaction product of a polymer and a cross-linking agent. Cross-linking is the formation of a chemical connection between polymer chains to form a three-dimensional network connecting molecules. The polymer can be selected from the list of the above-mentioned polymers. The cross-linking agent is well known in the art and can be selected according to the type of polymer.
[0064] In certain embodiments, the cross-linking agent is an acid selected from one or more of the following:
[0065] (i) dicarboxylic acids, including oxalic acid, malonic acid, succinic acid, glutaric acid, adipic acid, pimelic acid, suberic acid, azelaic acid, sebacic acid, malic acid, tartaric acid, tartronic acid, aspartic acid, glutamic acid, fumaric acid, itaconic acid, maleic acid, callic acid, camphoric acid, phthalic acid and its derivatives containing at least one boron or chlorine atom, tetrahydrophthalic acid and its derivatives containing at least one chlorine atom, isophthalic acid, terephthalic acid, mesaconic acid and citraconic acid,
[0066] (ii) tricarboxylic acids, including citric acid, tricarballylic acid, 1,2,4-butanetricarboxylic acid, aconitic acid, hemimetic acid, trimellitic acid and trimesic acid;
[0067] (iii) tetracarboxylic acids, including 1,2,3,4-butanetetracarboxylic acid and pyromellitic acid;
[0068] (iv) polycarboxylic acids such as EDTA;
[0069] (v) unsaturated carboxylic acids, including (meth)acrylic acid, crotonic acid, isocrotonic acid, maleic acid, cinnamic acid, 2-methylmaleic acid, fumaric acid, itaconic acid, 2-methylitaconic acid, α,β-methyleneglutaric acid and monoesters of unsaturated dicarboxylic acids; vinyl monomers are styrene optionally substituted with alkyl, hydroxyl or sulfonyl groups or substituted with halogen atoms, (meth)acrylonitrile, (meth)acrylamide optionally substituted with C1-C10 alkyl groups, alkyl (meth)acrylates, glycidyl (meth)acrylates, butadiene and vinyl esters
[0070] (vi) Inorganic acids such as boric acid and phosphoric acid.
[0071] In certain embodiments, the cross-linking agent is selected from the following list: primary amines (eg, N-hydroxysuccinimide esters), carbonyl compounds (eg, acrylic resins), inorganic acids (eg, phosphoric acid), Lewis acids (eg, boric acid or aluminum chloride), and carboxylic acids.
[0072] In certain embodiments, the crosslinking agent is a carboxylic acid selected from dicarboxylic acids, tricarboxylic acids, tetracarboxylic acids, polycarboxylic acids, and unsaturated carboxylic acids. In certain embodiments, the carboxylic acid is a polycarboxylic acid, such as citric acid or succinic acid. In certain embodiments, the carboxylic acid is an unsaturated carboxylic acid, such as acrylic acid, methacrylic acid, and maleic acid.
[0073] In certain embodiments, the binder is the reaction product of polyvinyl alcohol and citric acid. Carboxylic acids are a preferred type of crosslinking agent because of their low toxicity and cost. Polyvinyl alcohol is also known to be non-toxic and biodegradable.
[0074] In certain embodiments, the binder is present in an amount of about 0.1 wt % to about 40 wt % of the total weight of the microparticle, or about 1 wt % to about 35 wt % of the total weight of the microparticle, or about 5 wt % to about 30 wt % of the total weight of the microparticle, or about 10 wt % to about 25 wt % of the total weight of the microparticle, or about 15 wt % to about 20 wt % of the total weight of the microparticle, or about 1 wt % to about 5 wt % of the total weight of the particle.
[0075] In certain embodiments, the binder is composed of a polymer such that 100% by weight of the binder is a polymer. In certain embodiments, the binder further comprises a crosslinker in addition to the polymer component, and the weight ratio of the polymer component to the crosslinker is from 1:1 to 3:1; or from 1:1 to 3.5:1 or from 1:1 to 1:4. According to one embodiment, the polymer component is polyvinyl alcohol and the crosslinker is a carboxylic acid; the weight ratio of the polyvinyl alcohol to the carboxylic acid is from 1:1 to 3:1; or from 1:1 to 3.5:1 or from 1:1 to 1:4.
[0076] Method for preparing microparticles
[0077] In certain embodiments, particles comprising at least one of expanded ground perlite particles, diatomaceous earth particles, and sepiolite particles are mixed together. The binder is first dispersed in water and sprayed onto the particles comprising at least one of expanded ground perlite particles, diatomaceous earth particles, and sepiolite particles so that the particles aggregate and form microparticles. After the spraying step, a curing step is performed at a temperature of 80° C. to 120° C. The curing step is generally performed for a period of time so that the microparticles have dried and the binder has cured. After the curing step is performed, the moisture content of the microparticles is less than about 5% by weight of the microparticles, for example, less than about 3% by weight, or less than about 2% by weight. The curing step is performed for a period of time so that the moisture content reaches the desired level as described above, and can take up to 12 hours, or up to 8 hours, or up to 4 hours.
[0078] Absorbent Materials
[0079] According to the present invention, there is provided an absorbent material comprising microparticles as described herein. In certain embodiments, the binder is a cross-linked binder, which is the reaction product of a polymer and a cross-linking agent. This type of binder is particularly well suited for applications where the microparticles are used as absorbent material and additional hydrophobicity is required (e.g., when used for oil absorption).
[0080] The present inventors have discovered that, due to the improved absorption capacity of the microparticles, the absorbent material is particularly useful in methods for treating fluid spills. The term "fluid spill" refers to the undesired release of fluid into the environment, such as oil spills (e.g., spills from tankers or leaks at gas stations), water spills (e.g., soft drinks, acidic solutions, and alkaline solutions), chemical spills (e.g., organic and inorganic solvents), food spills (e.g., soups or sauces), and body fluid spills (e.g., blood, urine, and vomitus).
[0081] In some embodiments, the absorbent material may be used in a closed container for disposal of liquid hazardous waste materials.
[0082] In certain embodiments, the absorbent material absorbs up to 100% of the fluid spill by weight of the microparticles, such as up to 95%, or up to 90%, or up to 85%, or up to 80%, or up to 75%, or up to 70% by weight of the microparticles.
[0083] Animal feed composition
[0084] According to the present invention, there is provided an animal feed composition comprising microparticles as described herein. In certain embodiments, the animal feed composition comprises at least one nutrient. The term "nutrient" refers to the basic substances required for animal maintenance, growth, reproduction and good health, including carbohydrates, proteins, fats, minerals, vitamins and water. The main source of carbohydrates in animal feed is cereals, such as oats, wheat, barley, corn, sorghum, fodder and hay. Protein can be plant or animal derived, such as amino acids, oil cake meals, fish meal and meat scraps. Common fat sources include fish oil, seed derived oils such as linseed oil, sunflower, rapeseed oil (canola oil) and plant derived oils such as corn and soybeans. Minerals can include elements important for maintaining healthy and productive animal growth, such as sodium, calcium, phosphorus, sulfur, potassium, magnesium, manganese, iron, copper, cobalt, iodine, zinc, molybdenum and selenium. Vitamins can be water-soluble or fat-soluble, and are roughly divided into vitamins A, B, C, D, E and K.
[0085] The above list is not intended to be limiting and the skilled artisan is aware of the available nutrients and will be able to select and mix the nutrients to provide the animal with the required nutritional diet and will depend on the species of the animal.
[0086] In certain embodiments, the particulate binder for the animal feed composition is selected from the group consisting of polyvinyl alcohol, bentonite, sodium alginate, potassium alginate, lignin sulfonate, urea-formaldehyde condensate, agar, carrageenan, guar gum, cassia gum, xanthan gum, cellulose, gum arabic (gum arabic), microcrystalline cellulose, methyl cellulose, ethyl cellulose, sorbitan monolaurate, starch or starch-based derivatives, and combinations thereof, preferably wherein the binder is polyvinyl alcohol.
[0087] In certain embodiments, the animal feed consists only of the microparticles and does not contain any additional nutrients or ingredients. Therefore, an animal feed composition is provided so that the microparticles absorb and carry the liquid of interest for the desired animal feed. The liquid of interest can be water, or can be any liquid nutritional animal feed. Those skilled in the art know suitable liquid nutritional animal feeds, and can select the liquid of interest according to the animal to be fed.
[0088] In certain embodiments, the microparticles absorb up to 100% of the target liquid by weight of the microparticle, such as up to 95%, or up to 90%, or up to 85%, or up to 80%, or up to 75%, or up to 70% by weight of the microparticle.
[0089] In certain embodiments, the binder is present in an amount from about 0.1 wt % to about 40 wt % of the total weight of the animal feed composition, or from about 1 wt % to about 35 wt % of the total weight of the animal feed composition, or from about 5 wt % to about 30 wt % of the total weight of the animal feed composition, or from about 10 wt % to about 25 wt % of the total weight of the animal feed composition, or from about 15 wt % to about 20 wt % of the total weight of the animal feed composition, or from about 1 wt % to about 5 wt % of the total weight of the animal feed composition.
[0090] Example
[0091] Example 1
[0092] The following granules (in granulated or ungranulated form as described below) were used in the testing of this example:
[0093] Expanded Ground Perlite (EMP, available from Imerys)
[0094] diatomite
[0095] Binders used: Polyvinyl alcohol; bentonite and lignin sulfonate
[0096] 500 g of particles (expanded ground perlite or diatomaceous earth) were placed in a mixer (Eireich mixer). 25 g of binder was dissolved in 700 g of water. The final weight percent of binder was 5 weight percent of the total microparticles. The binder composition was then sprayed onto the particles using a simple commercial sprayer.
[0097] Table 1
[0098]
[0099] PSD laser
[0100] The particle size distribution (PSD) was determined using a Mastersizer 2000 from Malvern instruments.
[0101] D 50 is the average particle size (D) measured by laser diffraction (standard NFX-11-666 or ISO 13320-1). 50 ), and is the value of the median diameter obtained by sedimentation using a sedigraph (standard Afnor-X-11-683 or ISO 13317-3), as described above and in the examples. Reference can be made to the article G. Baudet and JPRona, Ind. Min. Mineset Carr. Les techn. June, July 1990, pp 55-61, which shows that the lamellar index is related to the average ratio of the largest dimension of a particle to its smallest dimension.
[0102] Absorption capacity
[0103] The Westinghouse method is used to calculate the absorption capacity (based on NV V19-002). To implement this method, the sample to be tested is introduced into a liquid through a sieving device. In this case, the liquid used is dioctyl adipate. The sample is then soaked for 20 minutes, after which the sample is removed and excess liquid is removed. The weight of the product before and after soaking is compared to calculate the absorption of the product.
[0104] Dust analysis
[0105] Dust analyzer Dustmon RD 100 (available from ) characterizes the dustiness of powders and particles.
[0106] DustMon RD 100 consists of a dosing control system (sample beaker with valve and tube), a sample collector, a light source and a detector. The sample is poured into the sample beaker. At the start of the measurement, the valve opens and the sample drips along the tube into the sample collector. The dust generated in the sample collector will be measured by the detector and the resulting dust index will be displayed.
[0107] The results provide a measure of the maximum dust concentration in % (0-100% of full dust concentration).
[0108] density
[0109] The bulk density of a sample is assessed by measuring the sample into a test tube and comparing the volume of the sample to the mass of the sample.
[0110] Specific surface area (SSA--BETm 2 / g)
[0111] The BET specific surface area is determined using a method based on standard NFX 11-621 entitled “Determination of the mass (surface surface) of powders by gas adsorption—BET method—Volume measurement by nitrogen adsorption at low temperature”.
[0112] The method uses a Micromeritics measuring device (purchased from Micromeritics Instrument Corp., USA), which includes a vacuum pump, a VacPrep 061 degassing section, a Tristar 3000S measuring section and a sample holder, a Mettler AG204 balance with an accuracy of 0.1 mg, a Dewar flask, a nitrogen adsorption gas, and a helium carrier gas.
[0113] Weigh the sample (to the nearest 0.1 mg) near the empty sample holder and record its mass M0 in g. Then introduce the previously homogenized powder sample into the sample holder using a funnel. Leave enough space (dead volume) between the sample and the top of the sample holder to allow the gas to circulate freely. Place the sample holder in one of the degassing stations and degas at 250°C under a primary vacuum of 10 Pa for about 20 minutes. After degassing, add a sufficient volume of nitrogen to the sample holder to avoid the introduction of air during the transfer of the sample holder from the degassing station to the measuring station.
[0114] The sample holder is then attached to the measurement station and a Dewar containing liquid nitrogen is placed around the sample holder. The BET measurement is started using the instrument control software. The instrument then automatically performs the following operations:
[0115] - Vacuum removal of nitrogen introduced for transfer of the sample holder;
[0116] - Leakage test;
[0117] - Add helium carrier gas;
[0118] - measuring said dead volume at ambient temperature;
[0119] -Measure the cold dead volume using liquid nitrogen;
[0120] -Helium vacuum removal;
[0121] - Leakage test;
[0122] - adding nitrogen at 950 mm Hg and measuring the saturation pressure; and
[0123] - Get analysis values.
[0124] The instrument's data acquisition and processing software draws the converted BET line from the 5 measured adsorption points. Remove the Dewar flask and then the sample holder. Return the device to ambient temperature, then weigh the sample again near the sample holder (with an accuracy of 0.1 mg) and record the weight as M2 in g. Calculate the mass M (in g) of the test portion of the sample according to the following formula:
[0125] M=M2-M0
[0126] The value M is then introduced into the software calculation program, which automatically calculates the BET specific surface area of the sample in m 2 / g.
[0127] Porosity
[0128] Porosity is the percentage of interstitial void space in a particle. It is calculated using the following formula:
[0129] Φ=V v / V T
[0130] where Φ is the porosity, Vv is the void volume, V T is the total volume.
[0131] Porosity is measured using mercury porosimetry, which characterizes porosity by forcing mercury into the pores. The standard test for mercury porosimetry is outlined in ASTM D4404-18.
[0132] Angle of repose
[0133] The angle of repose is measured using a manual powder flow tester (EFT-01) using ISO8398: 1989. The angle of repose is calculated as follows:
[0134] Θ=tan -1 h / r
[0135] where θ is the angle of repose, h is the height of the cone in cm, and r is the radius in cm.
[0136] A complementary measurement to the angle of repose is the dynamic angle of repose (or flow angle), which is measured using a Granudum. The GranuDrum instrument (available from GRANUTOOLS TM The Flow Analyzer (Flow Analyzer) is an automated powder flow measurement technique based on the principle of a rotating drum. The drum is a horizontal cylinder with transparent side walls and is half filled with a powder sample.
[0137] The drum rotates around its axis at an angular velocity between 2 and 70 rpm. In this case, the angular velocity is measured at 10 rpm and a CCD camera captures multiple snapshots. For the measured rotational speeds, the dynamic cohesion index is measured from the interface fluctuations and the flow angle, also called "dynamic repose angle" in the literature, is calculated from the average interface position. Low values of the flow angle correspond to excellent flowability.
[0138] Liquidity
[0139] Figure 1 The effect of absorption on powder flowability is shown. Powder flow, also known as flowability, is defined as the relative movement of a mass of particles between adjacent particles or along the surface of a container wall. In other words, powder flowability refers to the ability of a powder to flow in a desired manner in a specific device.
[0140] Figure 1 The effect of % liquid DOA on the angle of repose was measured to evaluate flowability. The following samples from Table 1 were tested:
[0141] Granular EMP + 5 wt% PVA, particle size 200-600 μm
[0142] Granular EMP + 5 wt% PVA, particle size 600-1700 μm
[0143] Granular EMP + 5 wt% bentonite, particle size 200-600 μm
[0144] Granular DE, particle size 200-600 μm
[0145] Granular EMP + 5 wt% lignin sulfonate, particle size 600-2500 μm
[0146] Expanded Perlite (Unground)
[0147] Table 1 and Figure 1 The data in show that when PVA is used as a binder to form microparticles according to the present invention, the powder samples achieve excellent absorption capacity (between 90% and 100%) and excellent flowability results.
[0148] Other inventive samples (3 to 5) showed lower absorption in some cases, but had improved flow properties compared to the non-granulated counterparts. Sample 6 showed no flow properties at all.
[0149] Lignosulfonates were shown to be able to bind EMP and certainly had a good angle of repose, even though the absorption was lower.
[0150] SEM images were taken of the following samples from Table 1; and Figure 2In the presentation:
[0151] a) Expanded and ground perlite
[0152] b) Granular EMP+PVA (200-600μm)
[0153] c) Granular EMP + lignin sulfonate (200-600μm)
[0154] d) Granular EMP + bentonite (200-600μm)
[0155] The equipment used was a SEM FEIQuanta 200 microscope. The SEM images all showed proper granulation of the primary EMP particles using various binders.
[0156] Example 2
[0157] Table 2
[0158]
[0159] The Westinghouse absorption test was conducted on various microparticles prepared using expanded granular perlite (200-600 μm) and the components listed above in Table 2. The Westinghouse method was as described above.
Claims
1. A microparticle comprising at least one of expanded ground perlite particles, diatomaceous earth particles and sepiolite particles and a binder, wherein: i) D of the expanded and ground perlite particles 50 From about 5 microns to about 40 microns; ii) D of the diatomaceous earth particles 50 From about 5 microns to about 40 microns; iii) D of the sepiolite particles 50 From about 5 microns to about 100 microns; iv) D of the microparticles 50 From about 150 microns to about 2000 microns; and The particles are bonded together by the binder, forming pores between the particles.
2. The microparticle according to claim 1, having: An angle of repose of up to about 38° as measured by angle of repose (funnel method) using an EFT-01 powder flow tester; An absorbent capacity of at least 150% as measured using the Westinghouse method described herein and utilizing dioctyl adipate as the absorbate; and a dust content of less than 10 as measured by a dust analyzer DustmonRD 100.
3. The microparticles according to claim 1 or 2, wherein the D of either or both of the expanded ground perlite particles and the diatomaceous earth particles is 50 From about 10 microns to about 30 microns.
4. The microparticles according to any one of claims 1 to 3, wherein the D of the sepiolite particles is 50 From about 10 microns to about 50 microns.
5. The microparticles according to any one of claims 1 to 4, wherein the D of the microparticles 50 From about 200 microns to about 600 microns, or from about 600 microns to about 1700 microns.
6. Microparticles according to any one of claims 1 to 5, wherein the binder is: (i) polymers; or (ii) a cross-linked binder which is the reaction product of a polymer and a cross-linking agent; or (iii) bentonite; or (iv) Lignin sulfonates.
7. The microparticle according to claim 6, wherein the polymer is selected from one or more of a water-soluble synthetic polymer, a natural water-soluble polymer and a polyol.
8. Microparticles according to claim 6 or 7, wherein the crosslinking agent is an acid selected from one or more of the following: (i) dicarboxylic acids, including oxalic acid, malonic acid, succinic acid, glutaric acid, adipic acid, pimelic acid, suberic acid, azelaic acid, sebacic acid, malic acid, tartaric acid, tartronic acid, aspartic acid, glutamic acid, fumaric acid, itaconic acid, maleic acid, callic acid, camphoric acid, phthalic acid and its derivatives containing at least one boron or chlorine atom, tetrahydrophthalic acid and its derivatives containing at least one chlorine atom, isophthalic acid, terephthalic acid, mesaconic acid and citraconic acid, (ii) tricarboxylic acids, including citric acid, tricarballylic acid, 1,2,4-butanetricarboxylic acid, aconitic acid, hemimetic acid, trimellitic acid and trimesic acid; (iii) tetracarboxylic acids, including 1,2,3,4-butanetetracarboxylic acid and pyromellitic acid; (iv) polycarboxylic acids, such as EDTA; (v) unsaturated carboxylic acids, including (meth)acrylic acid, crotonic acid, isocrotonic acid, maleic acid, cinnamic acid, 2-methylmaleic acid, fumaric acid, itaconic acid, 2-methylitaconic acid, α,β-methyleneglutaric acid and monoesters of unsaturated dicarboxylic acids; vinyl monomers are styrene optionally substituted with alkyl, hydroxyl or sulfonyl groups or substituted with halogen atoms, (meth)acrylonitrile, (meth)acrylamide optionally substituted with C1-C10 alkyl groups, alkyl (meth)acrylates, glycidyl (meth)acrylates, butadiene and vinyl esters (vi) Inorganic acids such as boric acid and phosphoric acid.
9. The microparticles of claim 6, wherein the binder comprises: (i) polyvinyl alcohol; or (ii) The reaction product of polyvinyl alcohol and a carboxylic acid, preferably, wherein the carboxylic acid is citric acid.
10. An absorbent material comprising microparticles according to any one of claims 1 to 9, wherein the binder is a cross-linked binder which is a reaction product of a polymer and a cross-linking agent.
11. A method for handling a fluid spill, the method comprising applying the absorbent material of claim 10 to the fluid spill such that the fluid is absorbed by the absorbent material.
12. An animal feed composition comprising the microparticles according to any one of claims 1 to 9.
13. The animal feed composition of claim 12, wherein the composition further comprises at least one nutrient.
14. An animal feed composition according to claim 12 or claim 13, wherein the binder is selected from polyvinyl alcohol, bentonite, sodium alginate, potassium alginate, lignin sulfonate, urea-formaldehyde, agar, carrageenan, guar gum, cassia gum, xanthan gum, cellulose, gum arabic (gum arabic), microcrystalline cellulose, methyl cellulose, ethyl cellulose, sorbitan monolaurate, starch or starch-based derivatives and combinations thereof, preferably, wherein the binder is polyvinyl alcohol.
15. A method of preparing microparticles as claimed in any one of claims 1 to 9, comprising spray drying the expanded ground perlite particles together with a binder and subjecting them to a curing step.
16. The microparticles according to any one of claims 1 to 5, wherein the binder comprises starch or starch-based derivatives and combinations thereof.
17. The animal feed composition of claim 14, wherein the binder comprises starch or starch-based derivatives and combinations thereof.
Citation Information
Patent Citations
Micronized perlite filler product
US20060075930A1